A clarion call for preventing taxonomical errors of dermatophytes using the example of the novel Trichophyton mentagrophytes genotype VIII uniformly isolated in the Indian epidemic of superficial dermatophytosis. Issue 1 (1st October 2018) - Nenoff, Pietro; Verma, Shyam B.; Uhrlaß, Silke; Burmester, Anke; Gräser, Yvonne
Summary: An alarming pan Indian increase in the incidence of superficial dermatophytosis has been noticed over the past 5‐6 years. Recent studies have demonstrated emerging predominance of Trichophyton ( T .) mentagrophytes as the causative organism in such cases. Interestingly, a distinct Indian genotype of T . mentagrophytes has been identified and recognised with the help of sequencing of the ITS region of the rDNA. That has, however, led to a basic confusion owing to the newly introduced taxonomy of dermatophytes in 2017. According to this most recently suggested classification and new taxonomy of dermatophytes, the former " T . mentagrophytes complex" is differentiated into T . mentagrophytes (zoophilic strains) and T . interdigitale (anthropophilic strains). We have noticed that in some recent studies the causative agent of the chronic, relapsing dermatophytosis outbreak in India has been described as T . interdigitale . In our opinion, it is very likely that these T . interdigitale strains isolated in Delhi and Chennai in India are indeed strains more closely related to the neotype of T . mentagrophytes and not strains of T . interdigitale . We therefore want to underscore the importance of a common nomenclature of species in accordance with the new taxonomy of dermatophytes. This would most likely facilitate better understanding of the issue amongst dermatologists and microbiologists in general. Mistaken identification of Trichophyton isolates not limited to India is very likely to occur due to the lack of appropriate molecular diagnosis which in turn is based on the already published data that presumably wrongly identify one species instead of the other.